2014
DOI: 10.1118/1.4884227
|View full text |Cite
|
Sign up to set email alerts
|

Size-specific dose estimate (SSDE) provides a simple method to calculate organ dose for pediatric CT examinations

Abstract: For organs fully covered within the scan volume, the average correlation of SSDE and organ absolute dose was found to be better than ± 10%. In addition, this study provides a complete list of organ dose correlation factors (CF(organ)(SSDE)) for the chest and abdominopelvic regions, and describes a simple methodology to estimate individual pediatric patient organ dose based on patient SSDE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
63
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 84 publications
(65 citation statements)
references
References 31 publications
1
63
0
1
Order By: Relevance
“…(4) and the correlation factors (CF organ SSDE ) for the thorax and abdominopelvic were adopted from the publication by Moore et al 25 A correlation factor for the brain (CF organ SSDE = 0.9 ± 0.1) was established based on the methodology described in Moore et al…”
Section: C Patient Examinationsmentioning
confidence: 99%
“…(4) and the correlation factors (CF organ SSDE ) for the thorax and abdominopelvic were adopted from the publication by Moore et al 25 A correlation factor for the brain (CF organ SSDE = 0.9 ± 0.1) was established based on the methodology described in Moore et al…”
Section: C Patient Examinationsmentioning
confidence: 99%
“…A patient‐specific phantom represents a realistic model enabling accurate estimation of organ‐level dose; however, the segmentation of patient images is time consuming and not feasible for clinical routine applications. A potential alternative for person‐specific organ dose estimation is to use a library of computational models where habitus‐specific phantoms could serve as alternative models covering various anthropometric and anatomical characteristics of patients . Several habitus‐dependent phantom series have been developed to perform patient‐specific dose estimation by matching anthropometric characteristics of patients, such as gender, age, height, and body weight .…”
Section: Introductionmentioning
confidence: 99%
“…A potential alternative for person-specific organ dose estimation is to use a library of computational models where habitus-specific phantoms could serve as alternative models covering various anthropometric and anatomical characteristics of patients. 8 Several habitus-dependent phantom series have been developed to perform patient-specific dose estimation by matching anthropometric characteristics of patients, such as gender, age, height, and body weight. [9][10][11] Stepusin et al 12 suggested to match patient's data to a computational phantom from a predefined library using height and weight matching for patient-specific CT dosimetry.…”
Section: Introductionmentioning
confidence: 99%
“…SSDE “…provides an estimate of the dose at the center of the scanned region (along z) in the patient” and is defined as the patient dose estimate that takes into account corrections based on patient size by AAPM Report 204 . Although SSDE has been shown to be a good substitute for organ dose in the context of abdominal scans, the work of AAPM Report 204 was limited only to body CT examinations.…”
Section: Introductionmentioning
confidence: 99%